WEBSITE QUALITY, BRAND TRUST, AND PRICE PERCEPTION IN SHOPEE CUSTOMER LOYALTY: THE MEDIATING ROLE OF SATISFACTION - Muhammad Iqbal Ismail; Denies Susanto; Indar Riyanto (Universitas La Tansa Mashiro, 2026)
This study aims to examine the influence of website quality, brand trust, and price perception on customer loyalty, with customer satisfaction as a mediating variable among Shopee e-commerce users in Indonesia. The research is motivated by the increasing competition in the e-commerce industry, which requires companies to strengthen customer loyalty through high-quality digital services, strong brand trust, and competitive pricing strategies. This study adopts a quantitative approach using a survey method involving 300 active Shopee users selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that website quality, brand trust, and price perception have positive and significant effects on both customer satisfaction and customer loyalty. Among the independent variables, price perception demonstrates the strongest direct influence on customer loyalty. Furthermore, customer satisfaction partially mediates the relationships between website quality, brand trust, price perception, and customer loyalty. These findings suggest that customer loyalty in e-commerce platforms is not solely driven by competitive pricing but also by reliable platform performance and strong brand credibility that collectively create a satisfying shopping experience. This study contributes to the literature on digital marketing and customer loyalty in the Indonesian e-commerce context and provides managerial insights for Shopee in designing sustainable strategies to enhance customer satisfaction and long-term loyalty.